2022
DOI: 10.3389/fsurg.2022.899649
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing international medical graduate research productivity for application to US neurosurgery residency and beyond: A survey of applicants, program directors, and institutional experience

Abstract: BackgroundThe authors investigated perceived discrepancies between the neurosurgical research productivity of international medical graduates (IMGs) and US medical graduates (USMGs) through the perspective of program directors (PDs) and successfully matched IMGs.MethodsResponses to 2 separate surveys on neurosurgical applicant research productivity in 115 neurosurgical programs and their PDs were analyzed. Neurosurgical research participation was analyzed using an IMG survey of residents who matched into neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Although IMGs were excluded from data analysis due to their research fellowships already being completed, we found that on average they had 24.4 publications that were PubMed-indexed, which shows the need for stronger application credentials given the lower match rate for IMGs. Mignucci-Jiménez et al showed that the research productivity of IMGs is considered superior to US graduates in the field of neurosurgery [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although IMGs were excluded from data analysis due to their research fellowships already being completed, we found that on average they had 24.4 publications that were PubMed-indexed, which shows the need for stronger application credentials given the lower match rate for IMGs. Mignucci-Jiménez et al showed that the research productivity of IMGs is considered superior to US graduates in the field of neurosurgery [10].…”
Section: Discussionmentioning
confidence: 99%
“…The current literature includes several recent studies and commentaries identifying the impact of IMGs in Dermatology and voices the need for a strategy to promote their inclusion in Dermatology residency programs 5‐7 . Additionally, a number of publications assessing recruitments of IMGs in General Surgery and Neurosurgery, report not only comparability in performance between IMGs and US graduates, 8 but also significantly longer periods invested in dedicated research and more published articles for the IMG pool 9 …”
Section: 2021 2020 Specialty N Total % N Total % N Total %mentioning
confidence: 99%
“…[5][6][7] Additionally, a number of publications assessing recruitments of IMGs in General Surgery and Neurosurgery, report not only comparability in performance between IMGs and US graduates, 8 but also significantly longer periods invested in dedicated research and more published articles for the IMG pool. 9 The inclusion of IMGs in a competitive residency like Otolaryngology encounters specific barriers. The prospective residents face the burden of immigration and undergo a period of personal adjustment.…”
mentioning
confidence: 99%
“…In the data we reported using the National Resident Matching Program Charting Outcomes, IMGs were not included. However, it is well known that IMGs often have years of research experience and a curriculum vitae brimming with abstracts, presentations, and publications, especially when applying to competitive specialties . From anecdotal and survey evidence, program directors are keenly aware of the higher research output from IMGs compared with the output of their US medical graduate counterparts .…”
mentioning
confidence: 99%
“…However, it is well known that IMGs often have years of research experience and a curriculum vitae brimming with abstracts, presentations, and publications, especially when applying to competitive specialties . From anecdotal and survey evidence, program directors are keenly aware of the higher research output from IMGs compared with the output of their US medical graduate counterparts . Without a numerical United States Medical Licensing Examination Step 1 score available to report, this trend will only intensify.…”
mentioning
confidence: 99%